Long-Term Preservation and Storage of Faecal Samples in Whatman® Cards for PCR Detection and Genotyping of Giardia duodenalis and Cryptosporidium hominis (2021)
ABSTRACT: Preservation and conservation of biological specimens, including faecal samples, is a challenge in remote areas or poor-resource settings where the cold chain cannot be maintained. This study aims at evaluating the suitability of filter cards for long-term storage of faecal samples of animal and human origin positive to the diarrhoea-causing protozoan parasites, Giardia duodenalis and Cryptosporidium hominis. Three commercially available Whatman® Filter Cards were comparatively assessed: the FTA® Classic Card, the FTA® Elute Micro Card, and the 903 Protein Saver Card. Human faecal samples positive to G. duodenalis (n = 5) and C. hominis (n = 5) were used to impregnate the selected cards at given storage (1 month, 3 months, and 6 months) periods and temperature (-20 °C, 4 °C, and room temperature) conditions. Parasite DNA was detected by PCR-based methods. Sensitivity assays and quality control procedures to assess suitability for genotyping purposes were conducted. Overall, all three Whatman® cards were proven useful for the detection and molecular characterisation of G. duodenalis and C. hominis under the evaluated conditions. Whatman® cards represent a simple, safe, and cost-effective option for the transportation, preservation, and storage of faecal samples without the need of the cold chain.